Hydrophobic modified high-performance hydroxypropyl methyl cellulose hybrid material
By using 4-hydroxycoumarin-based nanocomplex as a hydrophobic modifier in hydroxypropyl methylcellulose membrane materials, the problems of poor hydrophobicity and insufficient functionality of the material are solved, and the multiple performance improvement of the material and the expansion of application fields are achieved.
Patent Information
- Application Number
- CN202411956708.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-29
- Publication Date
- 2025-03-28
AI Technical Summary
In actual use, hydroxypropyl methylcellulose membrane materials have poor hydrophobicity, insufficient mechanical properties, lack of antibacterial activity, antioxidant activity and ammonia-sensitive discoloration functions, which limits its application scope.
The homemade 4-hydroxycoumarin-based nanocomplex is used as a hydrophobic modifier. By combining with hydroxypropyl methylcellulose, a high-performance hydroxypropyl methylcellulose hybrid material is formed, which improves its hydrophobicity, mechanical strength, toughness, antibacterial activity, antioxidant activity and ammonia-sensitive discoloration functions.
The multiple performance improvements of hydroxypropyl methylcellulose membrane materials have been achieved, including excellent hydrophobicity, mechanical properties and functionality, and has broadened its application in food packaging, smart materials, antibacterial materials and other fields.
Smart Images

Figure CN119708644A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cellulose composite materials, and in particular to a hydrophobically modified high-performance hydroxypropyl methylcellulose hybrid material. Background Art
[0002] Cellulose is rich in sources and widely distributed. It is renewable, biodegradable, non-toxic, has good biocompatibility and structural stability. Hydroxypropyl methylcellulose is an amorphous, water-soluble cellulose derivative with good film-forming properties. It is widely used in food packaging, medicine, cosmetics and other industries. However, due to the poor hydrophobicity, mechanical and barrier properties of hydroxypropyl methylcellulose film materials, and the lack of antibacterial activity, antioxidant activity, ammonia-sensitive color change and other functions, it is subject to certain restrictions in practical application. In order to solve the disadvantage of poor hydrophobicity of hydroxypropyl methylcellulose film materials, the commonly used method is to add a hydrophobic modifier to the film material. However, the addition of conventional hydrophobic modifiers is often difficult to effectively improve the mechanical strength, toughness, antibacterial activity, antioxidant activity, and ammonia-sensitive color change of hydroxypropyl methylcellulose film materials at the same time. Therefore, in order to solve the above-mentioned shortcomings of insufficient performance and functions of hydroxypropyl methylcellulose membrane materials, the present invention utilizes a self-made, novel hydrophobic modifier as a functional filler to improve the hydrophobicity, mechanical strength, toughness, antibacterial activity, antioxidant activity, ammonia-sensitive color change and other properties of hydroxypropyl methylcellulose membrane materials, create a hydrophobically modified high-performance hydroxypropyl methylcellulose hybrid material, and broaden its application in food packaging, intelligent materials, antibacterial materials, antioxidant materials, ammonia detection, biomedicine, environmental monitoring and safety and other fields. Summary of the invention
[0003] The purpose of the present invention is to provide a hydrophobically modified high-performance hydroxypropyl methylcellulose hybrid material in view of the deficiencies of the prior art. The hybrid material not only has excellent hydrophobicity, mechanical strength, toughness and other properties, but also has antibacterial activity, antioxidant activity, ammonia-sensitive color change and other functions, and has high practical value and economic value in the fields of food packaging, intelligent materials, antibacterial materials, antioxidant materials, ammonia detection, biomedicine, environmental monitoring and safety.
[0004] The technical solution of the present invention:
[0005] The present invention provides a hydrophobically modified high-performance hydroxypropyl methylcellulose hybrid material, characterized in that it is composed of the following components in parts by weight: 150 parts of hydroxypropyl methylcellulose and 3-9 parts of a hydrophobic modifier;
[0006] The hydrophobic modifier is a 4-hydroxycoumarin-based nanocomplex (the scanning electron microscope image of which is shown in Figure 1), the preparation method of which comprises the following steps:
[0007] (1) Disperse 16.21 parts of 4-hydroxycoumarin in 5000 parts of ethanol, stir at room temperature for 30 minutes to obtain a uniform 4-hydroxycoumarin dispersion for later use;
[0008] (2) Take 13.90 parts of ferrous sulfate heptahydrate and dissolve it in 1000 parts of deionized water to obtain a uniform ferrous sulfate solution for later use;
[0009] (3) Add the ferrous sulfate solution obtained in step (2) to the 4-hydroxycoumarin dispersion obtained in step (1), stir and react at room temperature for 10 minutes, then centrifuge, wash and dry in sequence to obtain a hydrophobic modifier.
[0010] The present invention also provides a method for preparing the above-mentioned hydrophobically modified high-performance hydroxypropyl methylcellulose hybrid material, comprising the following steps:
[0011] (1) Add 150 parts of hydroxypropyl methylcellulose to 5000 parts of deionized water, stir at 85°C for 60 minutes to obtain a uniform hydroxypropyl methylcellulose solution, cool to room temperature and set aside;
[0012] (2) Disperse 3-9 parts of the hydrophobic modifier in 1000 parts of deionized water, stir at room temperature for 10 minutes to obtain a uniform dispersion, and set aside;
[0013] (3) adding the dispersion obtained in step (2) to the hydroxypropyl methylcellulose solution obtained in step (1), stirring at room temperature for 30 minutes to obtain a uniform film-forming solution for later use;
[0014] (4) The film-forming liquid obtained in step (3) is poured into a plexiglass dish and dried in an oven at 55° C. for 24 h to obtain a hydrophobically modified high-performance hydroxypropyl methylcellulose hybrid material.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] The high-performance hydroxypropyl methylcellulose hybrid material prepared by the present invention not only has excellent hydrophobicity, mechanical strength, toughness and other properties, but also has antibacterial activity, antioxidant activity, ammonia-sensitive color change and other functions. The material preparation process is simple, environmentally friendly, low-cost, and suitable for large-scale production. It has high practical value and economic value in the fields of food packaging, intelligent materials, antibacterial materials, antioxidant materials, ammonia detection, biomedicine, environmental monitoring and safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1is a scanning electron microscope image of the hydrophobic modifier involved in the present invention;
[0018] Figure 2 This is a scanning electron micrograph of a cross section of the hydroxypropyl methylcellulose hybrid material prepared in Example 3. DETAILED DESCRIPTION
[0019] In order to better explain the present invention, the present invention is further explained in detail below in conjunction with specific examples, but the embodiments of the present invention are not limited thereto.
[0020] In the following specific embodiments and comparative example formulations and preparation methods, the 4-hydroxycoumarin is an analytically pure reagent provided by Shanghai Yien Chemical Technology Co., Ltd.; ferrous sulfate heptahydrate is an analytically pure reagent provided by Xilong Chemical Co., Ltd.; ethanol is an analytically pure reagent provided by Tianjin Fuyu Fine Chemical Co., Ltd.; and hydroxypropyl methylcellulose is a product provided by Shanghai Aladdin Biochemical Technology Co., Ltd. (item number: H108817-500g).
[0021] In the following specific examples and comparative examples, the hydrophobic modifier is a 4-hydroxycoumarin-based nanocomplex (see the scanning electron microscope image of the nanocomplex). Figure 1 ), the preparation method of which comprises the following steps: (1) dispersing 16.21 parts of 4-hydroxycoumarin in 5000 parts of ethanol, stirring at room temperature for 30 minutes to obtain a uniform 4-hydroxycoumarin dispersion for later use; (2) taking 13.90 parts of ferrous sulfate heptahydrate, dissolving it in 1000 parts of deionized water, obtaining a uniform ferrous sulfate solution for later use; (3) adding the ferrous sulfate solution obtained in step (2) to the 4-hydroxycoumarin dispersion obtained in step (1), stirring at room temperature for reaction for 10 minutes, and then centrifuging, washing and drying in sequence to obtain a hydrophobic modifier.
[0022] Example 1
[0023] A hydrophobically modified high-performance hydroxypropyl methylcellulose hybrid material, characterized in that it is composed of the following components in parts by weight: 150 parts of hydroxypropyl methylcellulose and 3 parts of a hydrophobic modifier.
[0024] The preparation method comprises the following steps:
[0025] (1) Add 150 parts of hydroxypropyl methylcellulose to 5000 parts of deionized water, stir at 85°C for 60 minutes to obtain a uniform hydroxypropyl methylcellulose solution, cool to room temperature and set aside;
[0026] (2) Disperse 3 parts of the hydrophobic modifier in 1000 parts of deionized water, stir at room temperature for 10 minutes to obtain a uniform dispersion for later use;
[0027] (3) adding the dispersion obtained in step (2) to the hydroxypropyl methylcellulose solution obtained in step (1), stirring at room temperature for 30 minutes to obtain a uniform film-forming solution for later use;
[0028] (4) The film-forming liquid obtained in step (3) is poured into a plexiglass dish and dried in an oven at 55° C. for 24 h to obtain a hydrophobically modified high-performance hydroxypropyl methylcellulose hybrid material.
[0029] Example 2
[0030] A hydrophobically modified high-performance hydroxypropyl methylcellulose hybrid material, characterized in that it is composed of the following components in parts by weight: 150 parts of hydroxypropyl methylcellulose and 6 parts of a hydrophobic modifier.
[0031] The preparation method comprises the following steps:
[0032] (1) Add 150 parts of hydroxypropyl methylcellulose to 5000 parts of deionized water, stir at 85°C for 60 minutes to obtain a uniform hydroxypropyl methylcellulose solution, cool to room temperature and set aside;
[0033] (2) Disperse 6 parts of the hydrophobic modifier in 1000 parts of deionized water, stir at room temperature for 10 minutes to obtain a uniform dispersion for later use;
[0034] (3) adding the dispersion obtained in step (2) to the hydroxypropyl methylcellulose solution obtained in step (1), stirring at room temperature for 30 minutes to obtain a uniform film-forming solution for later use;
[0035] (4) The film-forming liquid obtained in step (3) is poured into a plexiglass dish and dried in an oven at 55° C. for 24 h to obtain a hydrophobically modified high-performance hydroxypropyl methylcellulose hybrid material.
[0036] Example 3
[0037] A hydrophobically modified high-performance hydroxypropyl methylcellulose hybrid material, characterized in that it is composed of the following components in parts by weight: 150 parts of hydroxypropyl methylcellulose and 9 parts of a hydrophobic modifier.
[0038] The preparation method comprises the following steps:
[0039] (1) Add 150 parts of hydroxypropyl methylcellulose to 5000 parts of deionized water, stir at 85°C for 60 minutes to obtain a uniform hydroxypropyl methylcellulose solution, cool to room temperature and set aside;
[0040] (2) Disperse 9 parts of the hydrophobic modifier in 1000 parts of deionized water, stir at room temperature for 10 minutes to obtain a uniform dispersion for later use;
[0041] (3) adding the dispersion obtained in step (2) to the hydroxypropyl methylcellulose solution obtained in step (1), stirring at room temperature for 30 minutes to obtain a uniform film-forming solution for later use;
[0042] (4) The film-forming liquid obtained in step (3) is poured into a plexiglass dish and dried in an oven at 55° C. for 24 h to obtain a hydrophobically modified high-performance hydroxypropyl methylcellulose hybrid material.
[0043] Comparative Example
[0044] As a comparison standard for each of the above embodiments, the present invention provides a hydroxypropyl methylcellulose material prepared without a hydrophobic modifier, comprising the following steps:
[0045] (1) Add 150 parts of hydroxypropyl methylcellulose to 5000 parts of deionized water, stir at 85°C for 60 minutes to obtain a uniform hydroxypropyl methylcellulose solution, cool to room temperature and set aside;
[0046] (2) Add 1000 parts of deionized water to the hydroxypropyl methylcellulose solution obtained in step (1), and stir at room temperature for 30 minutes to obtain a uniform film-forming solution for later use;
[0047] (3) The film-forming solution obtained in step (2) is poured into a plexiglass dish and dried in an oven at 55° C. for 24 h to obtain hydroxypropyl methylcellulose material.
[0048] Structure and performance test:
[0049] The structure and performance tests were performed on the hydroxypropyl methylcellulose material prepared in the above comparative example and the hydroxypropyl methylcellulose hybrid material prepared in the example, wherein the cross-sectional morphology of the hydroxypropyl methylcellulose hybrid material was characterized by a SEM (SU-5000, Japan High-Tech Corporation) instrument; the tensile properties were tested in accordance with GB / T 1040-2006; hydrophobicity characterization: the water contact angle of the sample material was measured using a static contact angle tester; the antibacterial property of the material was tested in accordance with QBT2591-2003; the ammonia response test method was as follows: the sample material was exposed to an ammonia environment, and the color change of the sample material was observed.
[0050] The DPPH free radical scavenging experimental method is as follows: in the experimental group, 0.2 g of the membrane sample was cut into pieces and soaked in 5 mL of ethanol. After soaking for 24 h, 2 mL of the supernatant of the soaking solution was extracted and set aside; then, 1 ml of 50 mg / L DPPH solution was added to the 2 mL of the supernatant, and the mixture was shaken and placed in the dark at room temperature for 1 h; then, the absorbance of the mixture at 517 nm (denoted as A) was measured using an ultraviolet spectrophotometer. sample ); for the control group, 1 mL of 50 mg / L DPPH solution was added to 2 mL of ethanol, and the mixture was shaken and placed in the dark at room temperature for 1 h; then, the absorbance of the mixture at 517 nm (denoted as A) was measured by a UV spectrophotometer. control );DPPH free radical scavenging rate (%)=100*(A control -A sample ) / A control .
[0051] Table 1 Performance test data
[0052] Group Example 1 Example 2 Example 3 Comparative Example Tensile strength (MPa) 48.16 52.1 52.84 46.81 Tensile elongation at break (%) 14.66 15.44 17.45 14.03 <![CDATA[Toughness (MJ / m 3 )]]> 5.67 6.35 7.50 4.64 Water contact angle (°) 62.9 66.8 77.2 45.8
[0053] The cross-sectional morphology of the hydroxypropyl methylcellulose hybrid material prepared in Example 3 was observed and analyzed using a scanning electron microscope. It was found that the cross-sectional morphology was uniform, and no obvious agglomeration of the hydrophobic modifier was observed, which means that the hydrophobic modifier has good compatibility with the hydroxypropyl methylcellulose matrix, which is conducive to obtaining a high-performance hydroxypropyl methylcellulose hybrid material.
[0054] The results of the ammonia response test experiment show that the hydroxypropyl methylcellulose material prepared in the comparative example is colorless and transparent. After being exposed to an ammonia environment, its color does not change, and it still exhibits colorless and transparent optical properties; the hydroxypropyl methylcellulose hybrid material prepared in Example 3 is yellow, and after being exposed to an ammonia environment, its color changes to brown; the above results indicate that the hydroxypropyl methylcellulose hybrid material prepared in the example has excellent ammonia-sensitive color-changing function.
[0055] The results of the DPPH free radical scavenging experiment show that the DPPH free radical scavenging rate of the hydroxypropyl methylcellulose hybrid material prepared in Example 3 is 90.11%, indicating that it has excellent antioxidant activity, while the hydroxypropyl methylcellulose prepared in the comparative example has no obvious antioxidant activity.
[0056] The results of the antibacterial performance experiment show that the hydroxypropyl methylcellulose hybrid material prepared in Example 3 has an antibacterial rate of more than 99% against Escherichia coli and Staphylococcus aureus, indicating that it has excellent antibacterial activity, while the hydroxypropyl methylcellulose prepared in the comparative example has no obvious antibacterial activity.
[0057] The water contact angle results show that the hydroxypropyl methylcellulose hybrid material prepared in the example exhibits a significantly increased water contact angle due to the addition of the hydrophobic modifier, which proves that the hydroxypropyl methylcellulose hybrid material prepared in the example has significantly improved hydrophobicity compared to the hydroxypropyl methylcellulose material prepared in the comparative example.
[0058] In summary, it can be seen from the sample performance test data (see Table 1) that the hydroxypropyl methylcellulose hybrid material prepared by the present invention not only has excellent hydrophobicity, mechanical strength, tensile elongation at break (i.e. ductility), toughness, and other properties, but also has antibacterial activity, antioxidant activity, ammonia-sensitive color change and other functions. The preparation process of the hybrid material is simple, environmentally friendly, low-cost, and suitable for large-scale production. It has high practical value and economic value in the fields of food packaging, smart materials, antibacterial materials, antioxidant materials, ammonia detection, biomedicine, environmental monitoring and safety.
[0059] The content of the present invention is not limited to the embodiments listed, and any equivalent changes made to the technical solution of the present invention by ordinary technicians in this field after reading the description of the present invention are covered by the claims of the present invention.
Claims
1. A hydrophobically modified high-performance hydroxypropyl methylcellulose hybrid material, characterized in that: The method is composed of the following components in parts by weight: 150 parts of hydroxypropyl methylcellulose and 3-9 parts of a hydrophobic modifier; The hydrophobic modifier is a 4-hydroxycoumarin-based nanocomplex, and its preparation method comprises the following steps: (1) Disperse 16.21 parts of 4-hydroxycoumarin in 5000 parts of ethanol, stir at room temperature for 30 minutes to obtain a uniform 4-hydroxycoumarin dispersion for later use; (2) Take 13.90 parts of ferrous sulfate heptahydrate and dissolve it in 1000 parts of deionized water to obtain a uniform ferrous sulfate solution for later use; (3) Add the ferrous sulfate solution obtained in step (2) to the 4-hydroxycoumarin dispersion obtained in step (1), stir and react at room temperature for 10 minutes, then centrifuge, wash and dry in sequence to obtain a hydrophobic modifier.
2. The method for preparing a hydrophobically modified high-performance hydroxypropyl methylcellulose hybrid material according to claim 1, characterized in that The steps include: (1) Add 150 parts of hydroxypropyl methylcellulose to 5000 parts of deionized water, stir at 85°C for 60 minutes to obtain a uniform hydroxypropyl methylcellulose solution, cool to room temperature and set aside; (2) Disperse 3-9 parts of the hydrophobic modifier in 1000 parts of deionized water, stir at room temperature for 10 minutes to obtain a uniform dispersion, and set aside; (3) adding the dispersion obtained in step (2) to the hydroxypropyl methylcellulose solution obtained in step (1), stirring at room temperature for 30 minutes to obtain a uniform film-forming solution for later use; (4) The film-forming liquid obtained in step (3) is poured into a plexiglass dish and dried in an oven at 55° C. for 24 h to obtain a hydrophobically modified high-performance hydroxypropyl methylcellulose hybrid material.
3. The use of the hydrophobically modified high-performance hydroxypropyl methylcellulose hybrid material according to claim 1, characterized in that: Used in food packaging, smart materials, ammonia detection, environmental monitoring and safety fields.